2015
DOI: 10.1016/j.rboe.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous nerve injury during harvesting of one or two hamstring tendons for anterior cruciate ligament reconstruction

Abstract: ObjectiveThe aim of this study was to assess whether harvesting of two hamstring tendons (semitendinosus and gracilis) has the same rate of nerve injury as harvesting of the semitendinosus tendon alone, used as a triple graft.MethodsChanges in sensitivity relating to injury of the infrapatellar branch of the saphenous nerve were evaluated in 110 patients six months after they underwent anterior cruciate ligament (ACL) reconstruction using hamstring tendons. They were divided into two groups: one in which only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
(21 reference statements)
0
10
0
1
Order By: Relevance
“…Letartre et al, 20 to avoid injuries in the saphenous nerve and in its branches in the anteromedial district of the knee, suggested a technique that utilizes the posterior access for removing the flexor tendons. In another examination, de Padua et al 21 reported a lower rate of saphenous nerve injuries in patients in whom only the semitendinosus tendon was removed (thus preserving the gracile), when compared with the harvesting of both grafts. To evaluate the impact of the IPBSN position on dynamic knee mobility in 20 cadaver knees, Tifford et al 13 presumed that incisions in the anterior aspect of the knee should be made in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Letartre et al, 20 to avoid injuries in the saphenous nerve and in its branches in the anteromedial district of the knee, suggested a technique that utilizes the posterior access for removing the flexor tendons. In another examination, de Padua et al 21 reported a lower rate of saphenous nerve injuries in patients in whom only the semitendinosus tendon was removed (thus preserving the gracile), when compared with the harvesting of both grafts. To evaluate the impact of the IPBSN position on dynamic knee mobility in 20 cadaver knees, Tifford et al 13 presumed that incisions in the anterior aspect of the knee should be made in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Letartre et al 14 suggested a technique that uses the posterior access for removing the flexor tendons in order to prevent lesions in the saphenous nerves and its branches in the anteromedial region of the knee. In a recent publication, De Padua et al 15 found a lower rate of saphenous nerve lesions in cases where only the semitendinosus tendon was removed (thus preserving the gracile) when compared with harvesting of both grafts. Tifford et al 7 assessed the effect of IPBSN position on dynamic knee mobility in 20 cadaver knees and concluded that incisions in the anterior aspect of the knee should be made in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…During arthroscopy-assisted ACL reconstruction, the incidence rate of the injury of the IBSN is higher than that during arthroscopy procedure alone. In 2015, de Padua et al 12 reported that graft harvesting is not risk-free. While harvesting graft from hamstrings muscles for ACL reconstruction, Figueroa et al 3 pointed out that injury to the IBSN was electrophysiologically detected in 68% of knees.…”
Section: Discussionmentioning
confidence: 99%